2011
DOI: 10.1149/2.060202jes
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insertion Species on Nanostructured Open Framework Hexacyanoferrate Battery Electrodes

Abstract: Recent battery research has focused on the high power and energy density needed for portable electronics and vehicles, but the requirements for grid-scale energy storage are different, with emphasis on low cost, long cycle life, and safety. 1, 2 Open framework materials with the Prussian Blue crystal structure offer the high power capability, ultra-long cycle life, and scalable, low cost synthesis and operation that are necessary for storage systems to integrate transient energy sources, such as wind and solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
385
3
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 426 publications
(410 citation statements)
references
References 39 publications
16
385
3
6
Order By: Relevance
“…Considering these requirements, we have selected solid CuHCF as the positive electrode for the TREC because of its negative temperature coefficient ( À 0.36 mV K À 1 ), high specific charge capacity (60 mAh g À 1 ) compared with redox couples in solution, relatively low specific heat (1.07 JK À 1 g À 1 ), and ultra-low voltage hysteresis [19][20][21] to 70°C. Figure 2a shows the OCV change of the CuHCF electrode (50% state of charge), the Cu/Cu 2 þ (3 M) electrode and the full cell for each 10-°C increment when the voltage is set at 0 V at 10°C.…”
Section: Resultsmentioning
confidence: 99%
“…Considering these requirements, we have selected solid CuHCF as the positive electrode for the TREC because of its negative temperature coefficient ( À 0.36 mV K À 1 ), high specific charge capacity (60 mAh g À 1 ) compared with redox couples in solution, relatively low specific heat (1.07 JK À 1 g À 1 ), and ultra-low voltage hysteresis [19][20][21] to 70°C. Figure 2a shows the OCV change of the CuHCF electrode (50% state of charge), the Cu/Cu 2 þ (3 M) electrode and the full cell for each 10-°C increment when the voltage is set at 0 V at 10°C.…”
Section: Resultsmentioning
confidence: 99%
“…50 Based on the charge/discharge curves, overpotentials are low at 0.83C rate, which demonstrates low irreversibility. 58 Added to these properties is the fact that the potential of modified PBA electrodes generally varies 59 mV per logarithm unit of the alkaline ion concentration. 59,60 NiHCF and CuHCF display properties that are worth exploring in MEB.…”
Section: Prussian Blue Analoguesmentioning
confidence: 99%
“…We recently demonstrated promising results with a new family of battery electrode materials based on the common, inexpensive Prussian Blue pigment [8][9][10][11] . Electrodeposited thin films of these materials have received substantial study in the past for their electrochromic properties, beginning with the pioneering work of Neff 12,13 .…”
mentioning
confidence: 99%
“…The result is an extremely stable electrode: over 40,000 deep discharge cycles were demonstrated in the case of the Cu II -N C-Fe III/II cathode 10 . We later showed that related cathode materials including nickel hexacyanoferrate (Ni II -N C-Fe III/II ) 11 also have a very long cycle life when operated in a wide variety of aqueous alkali-ion electrolytes 8 , and that their reaction potentials can be controlled by altering their composition 9 .…”
mentioning
confidence: 99%